Short-chain free fatty acid receptors FFA2/GPR43 and FFA3/GPR41 as new potential therapeutic targets - Ulven, Trond (Frontiers in Endocrinology, 2012)
The deorphanization of the free fatty acid (FFA) receptors FFA1 (GPR40), FFA2 (GPR43), FFA3 (GPR41), GPR84 and GPR120 made clear that the body is capable of recognizing and responding directly to nonesterified fatty acid of virtually any chain length. Colonic fermentation of dietary fiber produces high concentrations of the short-chain fatty acids (SCFAs) acetate, propionate and butyrate, a process which is important to health. The phylogenetically related 7-transmembrane receptors free fatty acid receptor 2 (FFA2) and FFA3 are activated by these SCFAs, and several lines of evidence indicate that FFA2 and FFA3 mediate beneficial effects associated with a fiber-rich diet, and that they may be of interest as targets for treatment of inflammatory and metabolic diseases. FFA2 is highly expressed on immune cells, in particular neutrophils, and several studies suggest that the receptor plays a role in diseases involving a dysfunctional neutrophil response, such as inflammatory bowel disease (IBD). Both FFA2 and FFA3 have been implicated in metabolic diseases such as type 2 diabetes and regulation of appetite. More research is however required to clarify potential of the receptors as drug targets and establish if activation or inhibition would be the preferred mode of action. The availability of potent and selective receptor modulators is a prerequisite for these studies. The few modulators of FFA2 or FFA3 that have been published hitherto in the peer-reviewed literature in general have properties that make them less than ideal as such tools, but published patent applications indicate that the situation may soon improve, and that proper tool compounds will enable studies critical to validate the receptors as new drug targets.